Immunity passports, fundamental rights and public health hazards: a reply to Brown et al. Issue 10 (9th September 2020) - de Miguel Beriain, Iñigo; Rueda, Jon
Abstract : In their recent article, Brown et al analyse several ethical aspects around immunity passports and put forward some recommendations for implementing them. Although they offer a comprehensive perspective, they overlook two essential aspects. First, while the authors consider the possibility that immunological passports may appear to discriminate against those who do not possess them, the opposite viewpoint of immune people is underdeveloped. We argue that if a person has been tested positive for and recovered from COVID-19, becoming immune to it, she cannot be considered a hazard to public health and, therefore, the curtailment of her fundamental rights (eg, the right to freedom of movement) is not legitimate. Second, they omit that vaccine distribution will create similar problems related to immunity-based licenses. Vaccine certificates will de facto generate a sort of immunity passport. In the next phases of the pandemic, different immunity statuses will be at stake, because the need to identify who can spread COVID-19 is unavoidable. If a person does not pose a threat to public health because she cannot spread the infection, then her right to freedom of movement should be respected, regardless of how she acquired that immunity.